2018
DOI: 10.3892/mmr.2018.9097
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen‑like‑protein 1 promotes the invasion and metastasis of gastric cancer and is associated with poor prognosis

Abstract: The protective role of fibrinogen-like-protein 1 (FGL1) in liver injury has been reported previously. However, there are few studies on FGL1 expression in gastric cancer (GC) tissues, and the role of FGL1 in GC remains unclear. The aim of the present study was to investigate the correlation between FGL1 expression and prognosis in GC patients. Data was downloaded from The Cancer Genome Atlas database, and 50 pairs of GC tissues and the corresponding non-tumor tissues were collected between 2008 to 2011. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 24 publications
1
60
1
Order By: Relevance
“…Several recent studies have shown that FGL1 is signi cantly upregulated in NSCLC patients and is closely correlated to the poor prognosis of these patients [7,31,34,36]. Further, FGL1 may be an important factor involved in epithelial-mesenchymal transition by in uencing cell-cell adhesion and information transmission [37,38]. Our previous study also revealed that loss of FGL1 did not induce but inhibited epithelial-mesenchymal transition in PC9/GR cells [39].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several recent studies have shown that FGL1 is signi cantly upregulated in NSCLC patients and is closely correlated to the poor prognosis of these patients [7,31,34,36]. Further, FGL1 may be an important factor involved in epithelial-mesenchymal transition by in uencing cell-cell adhesion and information transmission [37,38]. Our previous study also revealed that loss of FGL1 did not induce but inhibited epithelial-mesenchymal transition in PC9/GR cells [39].…”
Section: Discussionmentioning
confidence: 92%
“…It has also been shown that STAT3 signaling is involved in the regeneration and apoptosis of liver injury [33,41,42], and phosphorylated STAT3 regulated the expression of Bax, Bcl-2, and cell cycle-regulatory genes (including c-fos, c-myc, and cyclin), indicating its role in cell proliferation and apoptosis [43]. Although overexpression of FGL1 has been con rmed in several tumors and contributes to poor prognosis [31,[36][37][38]40], FGL1 expression is downregulated in HCC, and loss of FGL1 may lead to the low differentiation of HCC cells [31,36,40]. This difference may be closely related to the differentiation of tumor cells [40] and their surrounding microenvironment [28,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of NPPA have been described as prognostic predictors in patients with chronic heart failure, but are also known to reflect the severity of left ventricular hemodynamic dysfunction [15]. It has been suggested that FGL1 plays a role in liver protection and liver regeneration, but it also has the potential to serve as a target for the treatment of gastric cancer and to predict gastric cancer prognosis [16]. In addition, CCL16, a human CC chemokine, has been shown to be differentially expressed in ovarian cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…FGL1 belongs to the fibrinogen family of proteins which includes fibrinogen, FGL-1, FGL-2 and clotting factors V, VIII and XIII. FGL-1 is predominantly expressed by the liver, and by human cancers including gastric cancer [153] where it is associated with poor prognosis. FGL-1's fibrinogen-like domain interacts with LAG-3 either at membrane-distal D1 or D2 domains, although the specific means by which the FGL-1-LAG-3 interaction inhibits antigen-specific T cell activation remain unclear.…”
Section: Tigit: Preclinical and Clinical Datamentioning
confidence: 99%